2016
DOI: 10.1136/gutjnl-2016-311909
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a fluorescent small-molecule enhancer for therapeutic autophagy in colorectal cancer by targeting mitochondrial protein translocase TIM44

Abstract: A novel NIR small-molecule autophagy-enhancer, IR-58, with mitochondria-targeted imaging and therapy capabilities was developed for CRC treatment. Additionally, TIM44 was identified for the first time as a potential oncogene, which plays an important role in autophagy through the TIM44-SOD2-ROS-mTOR pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Yuan et al reported that a strong IR‐783 signal was detected in prostate cancer tissues but not in normal tissues, and their research showed that IR‐783 staining was almost completely colocalized with MitoTracker (a mitochondrial‐selective probe) in cancer cells. Moreover, they also identified that the organic anion transporter polypeptide (OATP), which is highly expressed in cancer cells, mediates the uptake of heptamethine cyanine dyes such as IR‐780, MHI‐148 and IR58 into the mitochondria of tumour cells. These results all suggest that the anticancer property of IR‐783 is related to mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al reported that a strong IR‐783 signal was detected in prostate cancer tissues but not in normal tissues, and their research showed that IR‐783 staining was almost completely colocalized with MitoTracker (a mitochondrial‐selective probe) in cancer cells. Moreover, they also identified that the organic anion transporter polypeptide (OATP), which is highly expressed in cancer cells, mediates the uptake of heptamethine cyanine dyes such as IR‐780, MHI‐148 and IR58 into the mitochondria of tumour cells. These results all suggest that the anticancer property of IR‐783 is related to mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high levels of Beclin-1 presented good prognosis and longer survival (131, 135), and ATG10 downregulation was associated with cell migration and invasion of CRC cells (137). In addition, several compounds were recently demonstrated to suppress colorectal carcinogenesis through the induction of autophagy, including Salvianolic acid B and IR-58 (138, 139). Those findings indicate that promoting autophagy may probably provide an effective strategy for the treatment of CRC.…”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%
“…And this kind of NIR heptamethine dyes is proved to possess structure‐inherent cancer‐specific accumulation property, which is mediated through the organic anion‐transporting polypeptide (OATP) cellular membrane transporters . More importantly, some of these dyes have been demonstrated to target mitochondria and modulate intracellular oxidative state to enhance cell survival, or to induce therapeutic autophagy for colorectal cancer treatment, which provide the possibilities to develop ER stress inducer by targeting mitochondrial functions. In this study, we have synthesized a series of new NIR fluorescent dyes functioned with ester or amino acid groups on the mitochondria‐targeted heptamethine core, and identified NIR fluorophore that induced therapeutic ER stress in cancer cells.…”
mentioning
confidence: 99%